(untitled) (Journal of Hama University, 2022)
The aim of this study is to investigate and analyze the evolution of Syria’s external debt over the period 2011-2020, in addition to estimate and evaluate the levels of foreign indebtedness by studying and analyzing the evolution of external debt indicators and analysis of Syria’s ability to achieve external debt sustainability. In order to achieve the purpose of the study, the analytical approach was relied upon. This is based on data from the World Bank, UNCTAD and United Nations database. The study reached a set of results, the most important of which is that, despite the economic deterioration that Syria experienced in conjunction with the 2011 crisis, the external debt in Syria did not increase during the period of the crisis, and this indicates that Syria did not depend on borrowing from external sources to face its economic problems. Despite the deflation in the gross domestic product, and the decline in the value of exports, the levels of external debt in Syria are still within acceptable limits, as the value of debt indicators did not exceed their critical levels throughout the study period and Syria has the ability to bear external debt according to the World Bank-IMF debt sustainability Framework for Low-income Countries, but the non-performance of debt service payments and Syria’s failure to pay has led to a significant increase in the value of arrears, and work must be done to reorganize these debts.